The challenge in diagnosing Crohn’s disease in TB endemic region – A case report with review of literature (Bangladesh Journal of Medical Science, 2018)
The challenge in diagnosing the regional ileitis existed since 1932 when Crohn, Ginzberg and Oppenheimer first reported their case1. Many Indian researchers accepted that during last decade there was considerable increase in the incidence of Crohn’s disease (CD) in India which poses great challenge in diagnosing it, due to high prevalence of tuberculosis2. In this perspective we report a case which made a stimulus to review the literature. The purpose of this manuscript is 1. To document the occurrence of an additional case of CD in India, 2. To report that CD can rarely present as post operative enterocutaneous fistula, 3. To discuss the criteria in diagnosing the CD in Tuberculosis (TB) endemic area.Bangladesh Journal of Medical Science Vol.17(4) 2018 p.688-690